Analysis of Pneumatic Systems Using the Laplace Equation Based on Python Programing - Adhe Lingga Dewi; Rizwan Arisandi (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2023)
Analysis for Pneumatic Systems using the Python programming language on Google Colab has been carried out. The steps taken before the simulation are to design a pneumatic system and then determine the Laplace equation based on Bernoulli's law equation. The Python programming language on Google Colab was chosen because it allows users to type Python code in a web browser and can be used for free. The simulation is carried out by varying the value of capacitance (C) from 50 kPa - 300 kPa with an increase of 50 kPa. This aims to determine the effect of changes in capacitance variations on the pressure exerted on the pneumatic system. Based on the simulation results, the greater the capacitance variation given, the resulting graph will be more sloping or closer to the x-axis. The C = 50 kPa variation has a steeper graph, while the C = 300 kPa variation has a more sloping graph and is closer to the x-axis.